Factor Analysis Of Drop Out (Do) Basic Immunization In Gondang Community Health Center Of Bojonegoro Regency In 2017 - Putri, Evita Muslima Isnanda (Journals of Ners Community, 2018)
ABSTRACT In practice, immunization is done on a scheduled basis, this is done to facilitate the delivery and as a control to detect children who drop out of basic immunization. This study aims to analyze the factors of drop out of basic immunization at Gondang Community Health Center. This research uses analytic survey method with retrospective study approach. The population in this study is all mothers who have children aged 0-12 months in 2014. Samples were chosen by way of purposive sampling, obtained 48 respondents. Data analysis, editing, coding, scoring, tabulating and presented in tabular form. The result of this research shows that the order of the factors most related to the immunization drop out at the Gondang Community Health Center is the attitude (contingency coeffisient = 0,00) and the knowledge (contingency coeffisient = 0,037). It was concluded that mother's knowledge and attitude were significantly related to the complete drop out of basic immunization, while education, occupation and economic status were not significantly related to the complete drop out of complete immunization. To overcome the problem of complete drop out of basic immunization, active participation from health personnel (midwife) and mother is needed. For health workers, the delivery of information on immunization, the impact and timing of the implementation of immunization should always be delivered on an ongoing basis to the mother. Keywords: Drop Out Basic Immunization, ChildrenDOI: 10.5281/zenodo.2629501